Results on the Fractional Cumulative Residual Entropy of Coherent Systems - Tahmasebi, Saeid; Mohammadi, Reza (Revista Colombiana de Estadística, 2021)
Recently, Xiong et al. (2019) introduced an alternative measure of uncertainty known as the fractional cumulative residual entropy (FCRE). In this paper, first, we study some general properties of FCRE and its dynamic version. We also consider a version of fractional cumulative paired entropy for a random lifetime. Then we apply the FCRE measure for the coherent system lifetimes with identically distributed components.